Walter Ralph Steiner papers - Steiner, Walter Ralph, 1870-1942.
Photocopy of a fragment of a letter (1780 June 7) from John Paul Jones to Edmond Charles Genet; four letters (1866-1867) of Ellen Mason and Mary Ann Roberts relating to a Christian mission in Lahaina, Hawaii; typewritten transcript of a narrative by Francis A. Boyle describing his Civil War experiences as a prisoner at Point Lookout, Md., and Fort Delaware, Del.; and three letters (1909-1937) to Steiner relating to his autograph collection and bibliography by him on Civil War prison narratives.
In part, negative photocopy and typewritten transcripts.
Physician and collector of autographs.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Boyle, Francis A., -- 1838-1907.; Genet, Edmond Charles, -- 1763-1834 -- Correspondence; Jones, John Paul, -- 1747-1792 -- Correspondence; Mason, Ellen, -- active 1866 -- Correspondence; Roberts, Mary Ann, -- active 1866 -- Correspondence; Autographs -- Collections; Missions -- Hawaii -- Lahaina; Delaware -- History -- Civil War, 1861-1865.; Fort Delaware (Del.) -- History; Maryland -- History -- Civil War, 1861-1865.; Point Lookout (Md.) -- History; United States -- History -- Civil War, 1861-1865 -- Bibliography; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate; Collectors, Autograph; Physicians